MODERN METHODS OF TREATMENT OF PATIENTS WITH TUBALPERITONEAL INFERTILITY (World Bulletin of Public Health, 2024)
Infertile marriage is one of the important medical and social problems of modern society, despite the significant progress made in the diagnosis and treatment of infertile couples. Among the causes of female infertility, one of the most frequent forms is tubal-peritoneal (TPB) - 30-65%. The main causes of TPB are inflammatory diseases of the uterine appendages, including sexually transmitted infections (STIs); complicated abortions or childbirth; surgical interventions on the pelvic organs; multiple therapeutic and diagnostic manipulations. Changes in the fallopian tubes are reduced to complete or partial obstruction due to lesions of the epithelial and muscular layer, peritubar adhesions, contractile dysfunction. All this causes difficulty or impossibility to perceive the oocyte, its transport into the uterine cavity. The variety of causes of TPB, difficulties in its detection and conservative treatment require the search for more effective methods of diagnosis and treatment
Keywords: modern methods; tubal pregnancy; infertility